Phosphodiesterase-4 Modulation as a Potential Therapeutic for Cognitive Loss in Pathological and Non-Pathological Aging: Possibilities and Pitfalls - T. Hansen III, Rolf; Zhang, Han-Ting (Current Pharmaceutical Design, 2015)
Phosphodiesterases (PDEs) are a super family of 11 enzyme families responsible for the hydrolysis of the intracellular secondary messengers cyclic AMP (cAMP) and cyclic GMP (cGMP). PDE4, in particular, is highly expressed in brain regions involved with regulation of memory, anxiety, and depression, including the hippocampus, amygdala, and nucleus accumbens. Senescence has been shown to result in extreme dysregulation of the cAMP pathway in various brain regions. Thus, as a critical controller of intracellular cAMP levels, PDE4 may be a potential target for the treatment of senescence-related cognitive disorders, which could be pathological and/or non-pathological in origin. While there is great potential in the development of novel PDE4 inhibitors for treatment of senescentcognition impairment, there are also currently many pitfalls that need to be overcome. PDE4 has four subfamilies (PDE4A, B, C, and D) that are differentially expressed throughout the brain and body, as well as at least 25 splice variants derived from alternative splicing and multiple promoter sites. PDE4 subtypes have been shown to have differential effects on behavior, and cAMP itself has also been shown to play a contrasting role in behavior in different brain regions. This review will focus on what is currently understood about PDE4 in aging, the potential for PDE4 modulation as a cognitive therapy, and current pitfalls and limitations that need to be overcome in the PDE4 field. Overall, furthering our understanding of this incredibly complex pathway may one day assist with the development of novel therapeutics for both pathological and non-pathological cognitive disorders associated with senescence.
Keywords: pitfall